Airborne heavy metals in two cities of North Rhine Westphalia – Performing inhalation cancer risk assessment in terms of atmospheric circulation. (November 2017) - Dimitriou, Konstantinos; Kassomenos, Pavlos
Abstract: The main objective of this study was to examine the levels of four heavy metals (As, Cd, Pb and Ni) in PM10 samples collected in two urban background stations in Dortmund and Bielefeld, in relation to atmospheric circulation. Pollution roses, Conditional Probability Function (CPF) roses and backward air mass trajectory clusters were used to identify air currents associated with the importation of PM10 and of the included metal constituents. In addition, PM10, NO2, SO2, O3, As, Cd, Ni and Pb concentrations were analyzed by a Principal Component Analysis (PCA) to reveal major local emission sources of PM10 metal content. Traffic was the main emitter of PM10, As, Cd, and Pb in both cities, highlighting the existence of non-negligible lead quantities in unleaded gasoline, whilst nickel emissions were associated with heavy fuel oil combustion in industries and primarily for domestic heating. The created CPF roses and trajectory clusters were in good agreement, clearly revealing that eastern air currents enriched the locally produced PM10 load with additional aerosols from Eastern Europe. The concentrations of arsenic and cadmium were also enhanced by the arrival of air parcels from the East, indicating the anthropogenic origin of the exogenous aerosols due to combustion. The induced cancer risk (CRinh ) for adults, due to inhalation of individual metal constituents, was also estimated in terms of atmospheric circulation, indicating higher risk in Dortmund than in Bielefeld. CRinh values for arsenic exceeded the limit of 1 × 10 −6 in both cities, primarily during the influence of eastern circulation. Graphical abstract: Highlights: Traffic was the main emitter of PM10, As, Cd, and Pb in Dortmund and Bielefeld. Eastern airflows enhanced PM10, As and Cd levels in North Rhine Westphalia. Polar air masses increased local Ni emissions from fuel oil combustion for heating. Arsenic was the most harmful carcinogenic metal element in PM10. Higher cancer risk was indicated in Dortmund than in Bielefeld.